The Influence of Affordability, Service Quality, and Financial Education on Customers' Decisions to Use Savings Products at Sharia Banks in Medan - Sitorus, Siti Sarah; Nurul Inayah; Tuti Anggraini (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to determine the description and influence of affordability, service quality, and financial education on customer decisions. The research subjects are the residents of Medan City. The method used is a quantitative approach with a survey method through multiple linear regression analysis. The population in this study is the residents of Medan City, numbering 2,480,000 people, with a purposive sampling technique, resulting in a sample size of 100 people. The results of this study indicate that affordability, service quality, and financial education significantly influence customer decisions. Simultaneously, the results show that affordability, service quality, and financial education simultaneously influence customer decisions, with an influence of 75.1%.